Cross-Correlation of Soil Moisture and Stone Content and Their Spatial Pattern Across the Different Slope Aspects and Soil Depth - Hailu Kendie Addis; Baye Ayalew; Muuz Gebretsadik; Atikilt Abera; Legese Abebaw Getu; Amsalu K. Addis (Turkish Journal of Agriculture: Food Science and Technology)
The analysis of the spatial interrelationship between soil properties and slope aspect is vital for understanding the range of influence on soil depth, moisture, and stone content distribution. This study aimed to investigate the spatial interrelationship of topsoil moisture and stone content in different slope aspects and soil depth. The 53.7 km2 watershed was divided into a 500m by 500m grid using ArcGIS and 230 soil samples were collected. In each sampling point, the soil was taken at three soil depth classes (0–25cm, 25–60cm, and 60–100cm) using a cylindrical auger, then soil samples were tested to determine the percentage of topsoil moisture, and stone content. The spatial interrelationship between aspect, soil depth, topsoil moisture, and stone content was analyzed using the R and GS+ software. The study had shown non-significant effects of aspect on topsoil moisture, stone content, and soil depth. However, topsoil moisture tends to be higher on the north-facing slope, while stone content tends to be higher on the southeast-facing slope. The analysis of Local Moran’s I revealed that topsoil moisture, stone content, and soil depth were significantly autocorrelated. The cross-semivariogram analysis of soil depth with topsoil stone content depicted a negative spatial correlation. The experimental cross-semivariogram of soil depth versus topsoil moisture was positively fitted to the exponential function, whereas soil depth with topsoil stone content was best fitted to the Gaussian model. Overall, soil depth is the more influential factor than the slope aspect regarding topsoil moisture depletion and stone content distribution in the study watershed.